CARICOM : development of cured meat and sausage industry (Commonwealth Secretariat LondonGB, 1984)
Assesses the meat processing industry in ten CARICOM countries focusing on size of the market, the existing industry, level of imports, and livestock development. Makes long and short term recommendations for development of industry based on assessment. These relate to the upgrading of existing units in larger and smaller territories, and the integrated development of livestock and meat processing. Notes that the production of sausage casings would not be viable. Provides profile for a typical small scale 100 tonnes per annum processed meat plant. Contains detailed appendixes.
IDS